Influence of moderate electric fields on gelation of whey protein isolate - Rodrigues, Rui M. (2015)
Proteins are one of the food constituents most affected by heating, and some of the changes involve their unfolding, denaturation and gelation. Ohmic heating has often been claimed to improve the quality of foodstuffs due to its uniform heating and (putative) presence of a moderate electric field (MEF). However, this is still subject to discussion, so it is important to determine the effect of ohmic heating and of its MEF upon food constituents. Hence, the aim of this work was to evaluate the effects of MEF on denaturation, aggregation and viscoelastic properties of whey protein isolate (WPI), and compare them with those obtained via conventional heating under identical treatment conditions (up to 30 min at 85 °C). Results have shown that MEF interferes with whey protein unfolding and aggregation pathways at relatively high temperatures. MEF treatments have resulted in WPI solutions possessing more 8 and 10% of native β-Lactoglobulin and α-Lactalbumin, respectively, after 30 s of heating at 85 °C, when compared with a conventional heating method. Protein aggregates from MEF-treated WPI solutions presented a maximum increase in size of 78 nm, whereas conventional heating produced an increase of 86 nm. Unlike in conventional heating, aggregation of whey proteins during MEF was not sufficiently strong to form a true elastic gel network, since decreases in both storage and loss modulus were observed following MEF treatment. Our results suggest that MEF may provide a novel method for production of a whey protein matrix with distinctive gel-forming properties.